1989
DOI: 10.1111/j.1365-2621.1989.tb04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Odor Components of Human Breath After the Ingestion of Grated Raw Garlic

Abstract: The major odor components of finely grated, raw garlic in the air of the human mouth have been studied. Immediately after garlic ingestion, tests of the mouth air of six subjects revealed two major peaks that were positively identified as being ally1 mercaptan and diallyl disulfide; these findings are based on an evaluation of the fragment patterns of a GC-MS analysis and from the actual retention times of these authentic compounds. The ally1 mercaptan level was higher than the level of diallyl disulfide, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 6 publications
2
39
0
Order By: Relevance
“…Our observation was in agreement with previous studies. The presence of a trace amount of dimethyl disulfide in raw and heated garlic has been reported in literature (9,10). The presence of allyl methyl sulfide in both raw and heat-treated garlic has been reported in literature (10,11), and similar results were also obtained in this study.…”
Section: And Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our observation was in agreement with previous studies. The presence of a trace amount of dimethyl disulfide in raw and heated garlic has been reported in literature (9,10). The presence of allyl methyl sulfide in both raw and heat-treated garlic has been reported in literature (10,11), and similar results were also obtained in this study.…”
Section: And Discussionsupporting
confidence: 80%
“…On the other hand, Minami et al (4) have reported allyl mercaptan and diallyl disulfide as the main components of oral malodor after eating garlic .…”
mentioning
confidence: 99%
“…Urine from healthy individuals consuming garlic or onions contains N-acetyl-S-allylcysteine and N-acetyl-S-(2-carboxylpropyl)-cysteine (9)(10)(11). Allylmercaptane and diallyldisulfide have been found in human breath after ingestion of garlic (12,13).…”
Section: Active Compounds In Allium Vegetablesmentioning
confidence: 99%
“…During the digestive process, allicin quickly metabolizes into other sulphur compounds [3][4][5]. Thus far, bioavailability has only been measurable by breath studies, which have detected the presence of metabolites AM, AMS and DADS after oral consumption [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, bioavailability has only been measurable by breath studies, which have detected the presence of metabolites AM, AMS and DADS after oral consumption [5,6]. Only traces of allicin were found in blood after being incubated for five minutes [7].…”
Section: Introductionmentioning
confidence: 99%